Shock Protection of Portable Electronic Products: Shock Response Spectrum, Damage Boundary Approach, and Beyond - Suresh Goyal; Jim M. Papadopoulos; Paul A. Sullivan (Shock and Vibration)
The pervasive shock response spectrum (SRS) and damage boundary methods for evaluating product fragility and designing external cushioning for shock protection are described in detail with references to the best available literature. Underlying assumptions are carefully reviewed and the central message of the SRS is highlighted, particularly as it relates to standardized drop testing. Shortcomings of these methods are discussed, and the results are extended to apply to more general systems. Finally some general packaging and shock-mounting strategies are discussed in the context of protecting a fragile disk drive in a notebook computer, although the conclusions apply to other products as well. For example, exterior only cushioning (with low restitution to reduce subsequent impacts) will provide a slenderer form factor than the next best strategy: interior cushioning with a “dead” hard outer shell.